Hybrid Approach for Optimized Resource Allocation Load Balancing in Cloud Infrastructure - Anmol Sachdev, Vivek Kumar Verma, Rohit Kumar Gupta, Tarun Jain, Ankit Mundra (International Journal of Advanced Science and Technology, 2019)
Today number of application are increasing rapidly and almost every one of it requires cloud environment for providing more services to the users but for better user satisfaction loads are needed to be balanced. So, this project provides better algorithm for balancing loads in cloud environment. The methodology we adopted for this project was to first create specified number of Datacenter and Broker and then providing the number of Virtual Machines (VMs) and cloudlets. And then applying the algorithm for allocating VM to host and for allocating cloudlet to VM. After which we have calculated the estimated duration of the task. This paper proses an algorithm which gives us a better way of allocating the VMs to the appropriate hosts and cloudlet to the deserving VMs. And hence tasks will be forwarded to the capable server. As a result, proposed algorithm minimized the make span time of the system. Also, gives better throughput of the system.